Management of Recurrent Pregnancy-Related Pericarditis - Michel Ibrahim; Michael Fattouh; Alice Jacobs (Case Reports in Cardiology)
The evidence on recurrent pregnancy-related pericarditis is limited, and management strategies are based on case reports and expert opinion. We describe a patient with myopericarditis complicated by cardiac tamponade presenting shortly after her first pregnancy, which was then complicated by refractory recurrent pericarditis. She was treated with standard first line therapies, such as NSAIDs, corticosteroids, and colchicine, and eventually initiated on the purine analog, azathioprine. Out of fear of teratogenicity, she self-discontinued her maintenance medications and thereafter, her course was complicated by a recurrent flare of pericarditis during a subsequent pregnancy. Our case illustrates the significant burden on our patient due to the incessant nature of her disease and on the providers due to the therapeutic dilemmas associated with family planning and pregnancy. Further data is required on this unique clinical scenario, and patient-centered management by a multidisciplinary team is critical.